A gold-gold oil microtrench electrode for liquid-liquid anion transfer voltammetry. - Dale, SE; Chan, Y; Bulman Page, P; Barnes, E; Compton, R; Marken, F (2013)
Two flat gold electrodes are placed vis-à-vis with an epoxy spacer layer that is etched out to give a ca. 100 μm-deep electrochemically active trench. A water-insoluble oil phase, here the redox system N,N-diethyl-N'N'-didodecyl-phenylenediamine (DDPD) in 4-(3-phenylpropyl)-pyridine (PPP), is immobilized into the trench to allow anion transfer upon oxidation of DDPD (oil) to DDP⁺ (oil). In "mono-potentiostatic mode" quantitative transfer/expulsion of anions into the trench oil phase occurs. However, in "bi-potentiostatic mode" feedback currents dominated by rapid plate-to-plate diffusion normal to the electrode surfaces are observed. Comparison of "normal" diffusion and "lateral" diffusion shows that the rate of diffusion-migration charge transport across the oil film is anion hydrophobicity dependent.